Brincando para aprender ou aprender brincando: a ludicidade no cotidiano da creche - Jóia, Adelaide (2014)
This Research discusses the public policies of early childhood education regarding concepts of care and pedagogical practices in public daycare centers. The Research subject is the municipality of Caieiras, in the State of São Paulo, whose curriculum proposal has undergone changes since 2008, moving from a traditional form of care, in which the dichotomy between care and education was evidenced in the routine with schedules for care activities and educational activities for a proposal focusing on playing and apparently integrating care and education. The guiding question of this Research is: What is the place that playfulness occupies today in early childhood education institutions, attending children from zero to three years old, and what are the possible relations and contradictions established between theories pointing towards a comprehensive early childhood education and the current practices? The aim is to understand if, in the new configuration, the children who attend these places are really playing more and how the playing occurs. The methodological procedures used to conduct this case study Research were participant observation, semistructured interviews with educators, trainee, pedagogical coordinator, director and supervisor. The data systematization was based on three categories of analysis: 1) the relationship between the educators and the children of the daycare center; 2) educators views about playing; and 3) the professional development of the educators. The data analysis points towards a complex educational context with authoritarian dichotomized practices in an apparently playful scenario